DETERMINANTS OF FERTILITY INTENTIONS AMONG EVER-MARRIED WOMEN IN PAKISTAN: IMPLICATIONS FOR POPULATION GROWTH AND FAMILY PLANNING POLICIES - Sanam Wagma Khattak; Shehla Gul; Neelum (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the factors influencing fertility intentions among ever-married women in Pakistan, utilizing data from the Pakistan Demographic and Health Survey (PDHS) 2017-2018. The analysis focuses on a cross-sectional sample of women aged 15-49 from five regions: Punjab, Sindh, Khyber Pakhtunkhwa, Balochistan, and Islamabad. A binary logistic regression model is employed to explore the determinants of fertility intentions, considering both socio-economic and biological factors. The findings reveal that the number of surviving children, age at marriage, and contraceptive use are significant predictors of a woman’s desire to limit family size. Women in the middle and late reproductive age groups show varying levels of fertility intentions, with older women less likely to desire additional children. Additionally, urban women, those with higher education, and current contraceptive users are more inclined to limit their fertility. However, regional differences persist, with women in Islamabad more likely to limit their fertility compared to those in other regions. The study underscores the need for targeted family planning services, particularly in high-fertility areas, and highlights the importance of addressing social and economic disparities to achieve a broader decline in fertility rates across Pakistan. The findings suggest that while some progress has been made, significant challenges remain in ensuring that all women have the resources and support necessary to make informed decisions about their fertility, which is crucial for both individual well-being and broader socio-economic development.